Temozolomide Sensitizes MGMT-Deficient Tumor Cells to ATR Inhibitors - Jackson, Christopher B.; Noorbakhsh, Seth I.; Sundaram, Ranjini K.; Kalathil, Aravind N.; Ganesa, Sachita; Jia, Lanqi; Breslin, Hank; Burgenske, Danielle M.; Gilad, Oren; Sarkaria, Jann N.; Bindra, Ranjit S. (Cancer research (Chicago, Ill.), 2019)
O -methylguanine-DNA methyltransferase (MGMT) is an enzyme that removes alkyl groups at the O -position of guanine in DNA. MGMT expression is reduced or absent in many tumor types derived from a diverse range of tissues, most notably in glioma. Low MGMT expression confers significant sensitivity to DNA alkylating agents such as temozolomide, providing a natural therapeutic index over normal tissue. In this study, we sought to identify novel approaches that could maximally exploit the therapeutic index between tumor cells and normal tissues based on MGMT expression, as a means to enhance selective tumor cell killing. Temozolomide, unlike other alkylators, activated the ataxia telangiectasia and Rad3-related (ATR)-checkpoint kinase 1 (Chk1) axis in a manner that was highly dependent on MGMT status. Temozolomide induced growth delay, DNA double-strand breaks, and G -M cell-cycle arrest, which led to ATR-dependent phosphorylation of Chk1; this effect was dependent on reduced MGMT expression. Treatment of MGMT-deficient cells with temozolomide increased sensitivity to ATR inhibitors both and across numerous tumor cell types. Taken together, this study reveals a novel approach for selectively targeting MGMT-deficient cells with ATR inhibitors and temozolomide. As ATR inhibitors are currently being tested in clinical trials, and temozolomide is a commonly used chemotherapeutic, this approach is clinically actionable. Furthermore, this interaction potently exploits a DNA-repair defect found in many cancers. SIGNIFICANCE: Monofunctional alkylating agents sensitize MGMT-deficient tumor cells to ATR inhibitors.